The complete mitogenome of the moon crab Ashtoret lunaris (Forskal, 1775), (Crustacea; Decapoda; Matutidae). (3rd March 2016) - Tan, Mun Hua; Gan, Han Ming; Lee, Yin Peng; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the moon crab Ashtoret lunaris was obtained from a partial genome scan using the MiSeq sequencing system. The Ashtoret lunaris mitogenome is 15, 807 base pairs in length (70% A + T content) and made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a putative 956 bp non-coding AT-rich region. This A. lunaris mitogenome sequence is the first for the genus, as well as the family Matutidae and superfamily Calappoidea.